Leadership for World-Class Universities : Challenges for Developing Countries. - Altbach, Philip G. (Taylor & Francis, 2010)
Leadership for World-Class Universities reveals how "world-class" thinking and policy can help university leaders employ modern solutions to the challenges facing higher education today.